2019
DOI: 10.1038/s41598-019-39159-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of a combination of Hibiscus sabdariffa and Lippia citriodora polyphenols in overweight/obese subjects: A randomized controlled trial

Abstract: Plant-polyphenols have shown the capacity to ameliorate obesity-induced metabolic disturbances, both in cell and animal models, where most therapeutic approaches have failed. On the basis of previous research, a dietary supplement containing 500 mg of a combination of polyphenolic extracts from Lippia citriodora L. and Hibiscus sabdariffa L. (LC-HS), in the context of an equilibrated isocaloric diet, was evaluated in a double blind, placebo-controlled and randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…In agreement with our findings, several studies in humans and in animal models with botanical extracts or ingredients containing in part or fully verbascoside have shown significant cardiometabolic benefits. Recently, a dietary supplement containing verbascoside and anthocyanins have exhibited vascular and metabolic benefits in a randomized controlled trial with overweight and obese subjects [6,13]. Moreover, the consumption of low doses of an olive leaf extract containing verbascoside, secoiridoids and flavonoids during 5 weeks in high fat diet (HFD)-induced obese mice prevented the development of obesity, glucose intolerance, insulin resistance and endothelial dysfunction [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In agreement with our findings, several studies in humans and in animal models with botanical extracts or ingredients containing in part or fully verbascoside have shown significant cardiometabolic benefits. Recently, a dietary supplement containing verbascoside and anthocyanins have exhibited vascular and metabolic benefits in a randomized controlled trial with overweight and obese subjects [6,13]. Moreover, the consumption of low doses of an olive leaf extract containing verbascoside, secoiridoids and flavonoids during 5 weeks in high fat diet (HFD)-induced obese mice prevented the development of obesity, glucose intolerance, insulin resistance and endothelial dysfunction [46].…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, numerous plants have been used as traditional remedies against diverse metabolic disorders, including those associated with obesity [5]. In recent years, a growing number of studies have demonstrated the mechanisms by which plant compounds, especially polyphenols, confer such benefits [6][7][8][9][10][11][12][13]. Approaches such as bioguided fractionation and purification have been used to identify the compounds responsible for the health effects, but are insufficient to resolve the complexity of plant extracts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A controlled before–after trial conducted by Ghislain et al () showed that 1 L of H. sabdariffa juice (containing 21.5‐g dried herbs) consumption per day for eight consecutive days could significantly decrease the serum HDL‐C level ( p = .005 vs. baseline), and even on the fourth day after drinking, the trend of HDL‐C decline is very obvious ( p = .003 vs. baseline; Ghislain et al, ). A trial conducted by Herranz‐López et al () showed that a combination of H. sabdariffa and Lippia citriodora polyphenols could improve cardiac metabolic parameters in obese patients, but long‐time consumption (2 months) might reduce the serum HDL‐C level ( p < .05 vs. baseline; Herranz‐Lopez et al, ). Nevertheless, the results of most animal experiments showed that H. sabdariffa or its extracts could increase HDL‐C or had no significant effect, instead of lowering it (Hopkins et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms are not well known (14)(15)(16). Scienti c literature shown that certain plan-derivate extracts such a Hibiscus sabadariffa, Lippia citriodora extracts can modulate different metabolic pathways and activating the AMPK pathway which favor lipolysis and therefore fat loss (17). Previous studies have shown that Hibiscus sabdariffa have an effect on the expression of pre-pandial hormones (18), containing a large amount of polyphenols that provide proven health bene ts (19), but its potential as a satiety agent is not deeply studied.…”
Section: Introductionmentioning
confidence: 99%